MIXED TOMATO AND SWEET STARFRUIT JUICE AGAINST THE FAMILY PLANNINGACCEPTOR'S BLOOD PRESSURE - Candra Wahyuni; Erma Retnaningtyas (Universitas Karya Husada Semarang, 2024)
Hypertension can be referred to as a condition when the systolic blood pressure exceeds 140 mmHg and the diastolic blood pressureexceeds 90 mmHg, as measured on two occasions with a five-minute interval, while the individual is in a state of sufficient rest andcalm. The use of 3-month injectable birth control containing progesterone can increase blood pressure. Increased blood pressure inbirth control participants can be overcome pharmacologically and non-pharmacologically. The aim of the investigation was to analyzethe administration of a mixture of tomato juice (Solanum lycopersicum) and star fruit (Averrhoa carambola L.) Against lowering bloodpressure in injectable Kb acceptors for 3 months. The research design used an experimental approach one group pretest and posttest.Sampling technique with purposive sampling, the number of samples is 30 people. The statistical test employed is the t-test. Theresearch showed 24 (80%) respondents had a decrease in blood pressure and 6 (20%) respondents had a fixed blood pressure withan average systole change of 130.00 mmHg and diastole 85.17 mmHg. The findings of Paired Samples T-Test obtained a significancevalue of 0.000 (p < 0.05) which means that there is an influence of giving a mixture of Tomato Juice (Solanum lycopersicum) and StarFruit (Averrhoa Carambola L.) At acceptor kb inject 3 months. This is influenced by the content of potassium as an antidiuretic so thatit can reduce sodium levels in the urine by the kidneys